Prevalence of possible sarcopenia in community-dwelling older Chinese adults: a cross-sectional study - Lin Yang; Lingyan Li; Hongyu Wang; Jiaqin Yao; Yaoting Wang; Mengting Ren (BMJ Open)
Objectives To determine the prevalence of possible sarcopenia and its association with other conditions in older adults in Bengbu, China.Design, setting and participants A cross-sectional study of 1082 community-dwelling Chinese people aged at least 60 years from March to June 2022.Methods Handgrip strength and information regarding associated conditions were collected. Possible sarcopenia was estimated based on handgrip strength with cut-off values (<28 kg in men; <18 kg in women) recommended by the Asia Working Group for Sarcopenia in 2019. Mann-Whitney U tests, χ2 tests and binary logistic regression analyses were used to explore relationships between possible sarcopenia and associated conditions.Results Possible sarcopenia was more prevalent in men (52.79%, n=246, age 79.43±7.33 years among men with possible sarcopenia) than in women (44.48%, n=274, age 78.90±7.71 years among women with possible sarcopenia). In men, possible sarcopenia positively correlated with high age (OR 2.658, 95% CI 1.758 to 4.019), physical inactivity (OR 2.779, 95% CI 1.646 to 4.691) and diabetes (OR 4.269, 95% CI 2.397 to 7.602), and negatively with hypertension (OR 0.586, 95% CI 0.384 to 0.893). The risk of possible sarcopenia in men decreased by 12.6% for every 1 kg/m2 increase of body mass index (OR 0.874, 95% CI 0.817 to 0.935). In women, possible sarcopenia positively correlated with high age (OR 3.821, 95% CI 2.677 to 5.455), physical inactivity (OR 2.185, 95% CI 1.488 to 3.210) and arthritis (OR 2.076, 95% CI 1.411 to 3.056).Conclusion Possible sarcopenia is prevalent in older adults and the factors affecting possible sarcopenia are different in men and women. Health education about these target factors can be considered as a potential measure to prevent possible sarcopenia.